Trzy notatki o miejscach i tematach wartych do-czytania - Brzozowski, Jacek (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The first two sections of the paper draw attention to some incompletely interpreted issues within two Romantic dramas: the unclear status of the protagonist in Dziady, Part IV (on the one hand, representing the indefinability of man and, on the other, constituting the illustration of how lightly one may lose consistency and identity), and the ambiguous relationship between Goplana and Grabiec in Balladyna (which can be perceived in terms of the complex relations between ‘the angelic soul and the bluff head’ (dusza anielska i czerep rubaszny). The third section of notes is an encouragement to discuss two topics: ‘From Zygmunt Krasiński’s Leonard to Jerzy Andrzejewski’s Diego de Manente’; ‘From Pierścień Wielkiej-Damy, czyli: Ex-machina-Durejko by Cyprian Norwid to Tango by Sławomir Mrożek’.